Recent advances in transparent reflectarray antennas - Abbasi, Muhammad Inam; Kamarudin, Muhammad Ramlee; Ahmed Mugheri, Altaf; Mohd Ibrahim, Imran; Kiani, Saad Hassan; Dahri, Muhammad Hashim; Kamarudin, Muhammad Ramlee; Shamsan, Zaid Ahmed; Abbasi, Qammer Hussain (Institute Of Electrical And Electronics Engineers Inc., 2025)
Transparent Reflectarray Antennas (TRAs) have emerged as a promising solution for next-generation communication systems requiring both electromagnetic performance and optical transparency. This review focuses on a detailed latest work on unit cell design innovations, material engineering, and performance optimization across microwave, millimeter-wave, and terahertz frequency bands. Key developments include the use of fine metal lines (FML), frequency selective surfaces, indium tin oxides (ITO) films, and liquid crystal-based reconfigurable structures to achieve wide phase tuning, low reflection loss, and high transmittance. Various fabrication techniques, such as photolithography on quartz and soda-lime glass substrates, have enabled lightweight and high-efficiency RA structures suitable for integration into smart windows, satellite platforms, and 6G communication devices. Additionally, transparent beam-steering mechanisms using anisotropic liquid crystal (LC) materials and metallic mesh frameworks demonstrate the feasibility of dynamic control while maintaining optical clarity. The paper also discusses current challenges—such as optical loss, material limitations, and fabrication complexity—and outlines future directions aimed at enhancing bandwidth, reconfigurability, and multifunctional performance of TRAs